La familia como apoyo a la inclusión educativa de estudiantes con discapacidad en la universidad :Caso: Universidad Politécnica Salesiana. - Castillo Ordóñez, Tatiana Estefanía (2017)
The present investigation project was made at the Politécnica Salesiana University of Quito, with the objective of identify the support families give to students with disabilities, for which a representative sampling of families was selected who gave information through a participative construction of the student story and their family environment using mapping technique. As important results of this investigation the support given by families to the their disability children during their university stage is highlighted, it still be significant and of great value in the inclusion with university processes, despite their participation not be as close as previous academic processes, relationship with the university, has favored to the educational incorporation within the same, allowing then become responsible of their own academic process.